Practicing sectarianism : archival and ethnographic interventions on Lebanon - Deeb, Lara; Nalbantian, Tsolin; Sbaiti, Nadya (Stanford University Press, 2023)
Practicing Sectarianism explores the imaginative and contradictory ways that people live sectarianism. The book's essays use the concept as an animating principle within a variety of sites across Lebanon and its diasporas and over a range of historical periods. With contributions from historians and anthropologists, this volume reveals the many ways sectarianism is used to exhibit, imagine, or contest power: What forms of affective pull does it have on people and communities? What epistemological work does it do as a concept? How does it function as a marker of social difference? Examining social interaction, each essay analyzes how people experience sectarianism, sometimes pushing back, sometimes evading it, sometimes deploying it strategically, to a variety of effects and consequences. The collection advances an understanding of sectarianism simultaneously constructed and experienced, a slippery and changeable concept with material effects. And even as the book's focus is Lebanon, its analysis fractures the association of sectarianism with the nation-state and suggests possibilities that can travel to other sites. Practicing Sectarianism, taken as a whole, argues that sectarianism can only be fully understood—and dismantled—if we first take it seriously as a practice. -- Présentation de l'éditeur.